Water sourcing by riparian tree species in ephemaral rivers - Schachtschneider, Klaudia (Department of Biological Sciences, 2014)
In arid southern Africa, many rivers are ephemeral, and surface flow occurs for less than 10% of the year. Floods, which occur erratically, recharge groundwater resources on which riverine vegetation depends. Trees and shrubs are the most common life forms along these river systems, because surface flows are too erratic for aquatic organisms to flourish. There is concern that alterations to the current water regime of ephemeral rivers will affect the distribution of riparian vegetation as trees provide valuable fodder, shade, firewood and construction material in otherwise inhospitable surroundings. Climate change, population growth and development needs all place growing pressure on these water-limited ecosystems. Careful catchment management is essential to meet human water needs without jeopardising the ecosystems. This is easier said than done however, as ephemeral river ecology and functioning are hardly understood. Their unpredictable hydrology, strong groundwater association, often remote location and the presence of large terrestrial life forms make ephemeral rivers difficult to understand and current âEnvironmental water allocationâ methods for wetter systems are unsuitable. Alternative methods are being developed, but to date they still have a strong emphasis on aquatic life forms and riparian vegetation is still insufficiently addressed. This study provides an ecophysiological perspective on the water sources and drought tolerance levels of four key riparian tree species in Southern Africa. The aim is to contribute to an improved understanding of the interrelationships between river flow, groundwater and use of water by trees. Stable Hydrogen and Oxygen isotope results show that the three key species along the Kuiseb River (Acacia erioloba, Faidherbia albida and Tamarix usneoides) do not take up any water from the regularly occurring fog events. Instead, they depend on a seasonally fluctuating mix of shallow and deep soil moisture as well as groundwater. All these water sources rely on regular recharge from floods. It suggests that reductions in flood frequency and especially in magnitude and duration will reduce groundwater recharge and affect species productivity and survival. It was investigated why A. erioloba, growing in the presence of the alien Prosopis glandulosa, show high mortality rates. The study used stable 2H, 18O and 13C isotopes, xylem pressure potentials and percentage canopy dieback to conclude that within the riparian zone, the two species depend on the same water sources and that indigenous A. erioloba are 2 significantly more water stressed when growing alongside P. glandulosa. Further inland A. erioloba is entirely groundwater dependent while P. glandulosa seasonally switches between water sources. This resource partitioning is advantageous for A. erioloba, which does not display the same levels of water stress as in the riparian zone. An investigation into the physiological structure, including wood density, xylem vessel diameters and xylem vulnerability to cavitation for all four species showed that A. erioloba was structurally the most drought tolerant. This finding corresponded well with its high survival rate in the 1980s Namib drought. In the Kalahari, however, it is still outcompeted by P. glandulosa, suggesting that the invasive species has a competitive edge over A. erioloba that goes beyond xylem structure. P. glandulosa and T. usneoides are similar in structure. F. albida is structurally the most vulnerable of the species, supporting the high mortality rates observed in the 1980âs. Water sourcing using stable Hydrogen and Oxygen isotopes, xylem structure and phenology were compared for three A. erioloba stands with access to different groundwater depths (4 m, 21 m and 56 m). The aim was to determine whether A. erioloba physiology changed proportionally to groundwater depth. Results show that A. erioloba structure and phenology do respond proportionally to groundwater depth, suggesting that A. erioloba can reach deep groundwater, but that this comes at a cost of increased water stress and reduced vitality. Ttrees depending on deep groundwater may thus be closer to a water-induced survival threshold than those growing with access to shallower groundwater. Catchment managers should carefully weigh up the benefits of new water developments relative to potential losses of this ecologically and economically important species. As the final objective and synthesis this study aimed to evaluate if any of the studied species could be used as a bioindicator for tree health in relation to water availability. T. usneoides was previously observed to be less tolerant to drought conditions than F. albida and A. erioloba, while this study has shown F. albida to be structurally the most vulnerable. Hence no bioindicator could be indentified and it is concluded that the determination of drought tolerance and the identification of one or more bioindicator species for future monitoring is a complex matter that needs to include more structural studies and field documentation during drought. 3 Ultimately the use of indicator species and investigations into water sourcing as well as drought tolerance studies should inform catchment management and be included in future assessments of environmental water requirements (EWR) methods and river health. This study concludes that several of the methods applied in this study (shoot growth measurements, percentage canopy dieback, wood density, Î´2H, Î´18O and Î´13C stable isotopes, xylem pressure potentials and xylem vessel diameters) are worth applying in in a EWR in conjunction with groundwater and flood (volume, duration and height) measurements. This will require a shift from a traditionally aquatic outlook to one that is more inclusive of terrestrial ecology. More interdisciplinary cooperation and lateral thinking between aquatic and terrestrial ecologists is crucial, so that the frequency, magnitude, predictability and duration of floods and associated groundwater recharge are assessed in terms of water needs of woody riparian species as well as the associated terrestrial fauna.